Impact of China-Pakistan Economic Corridor (CPEC) on China's Interests in Pakistan’s Domestic Policies - Christina Rosa Jeen; Fredy Buhama Lumban Tobing (Poltanesa, 2025)
Through South-South Cooperation, China develops opportunities for political and economic development in southern countries. This study wants to focus more on the influence of bilateral cooperation in the form of CPEC foreign aid by China in Pakistan, which influences Pakistan's domestic and foreign political policies related to the interests of the Chinese state. So the question of this study is how does CPEC aid affect the attitude of the Pakistani government that supports the Chinese government at the domestic level of Pakistan? In this research, the influence of Michel Foucault's theory of power will be explained. The use of deductive qualitative analysis, in which the researcher uses existing theories and then analyzes the data obtained with Michel Foucault's Power influence theory on China's foreign aid to Pakistan. The data collection technique through library studies is data collection by understanding and studying theories from various literature related to these cases. The results obtained from this study are the construction of Gwadar airport, which is more profitable for China. The Pakistani government tends to disregard the fate of the Uyghur ethnic group when UNHCR Pakistan does not extend the Uyghur refugee card, so that the Pakistani government deports the refugees. Then, the emergence of bride trafficking cases after easy access between China and Pakistan resulted in public protests and dissatisfaction with the ongoing CPEC cooperation, which was considered asymmetrical.